Government Capacity in Coping with Covid-19 in Bandung City - Leo Agustino; Mona Sylviana; Ayuning Budiati (Pusjar SKPP Lembaga Administrasi Negara, 2021)
This article analyzes the capacity of the Bandung City Government to handle the COVID-19 pandemic. There is a gap between the policies implemented and the high curve of the spread of the virus in Bandung city. This study used a qualitative approach, and the data sources were from various documents, observations, and interviews. This article finds two factors that influence the capacity of the Bandung City Government: (i) the relationship between the central government and regional governments and (ii) the capacity of individuals to process information and exercise discretion. The weak capacity of the Bandung City Government affects trust, which has implications for the low participation of Bandung City residents. The article that elaborates on the state (government) capacity approach from Williams (2019) shows that individual capacity directly affects government capacity in crisis conditions, such as the COVID-19 pandemic.